Transparency in fiscal and monetary policy in Trinidad and Tobago - Forde, Penelope (2001)
Explores the various meanings of governance since the critical 1992 study by the World Bank and takes a closer look at one of the four pillars ascribed to governance by the international financial institutions. Examines governance in respect of the Codes of Conduct which have been drawn up to support monetary and financial issues. Closes with an initial assessment of adherence to these Codes of Conduct in Trinidad and Tobago.